Analysis of Medical Record Documentation and Diagnosis Coding in Orthopedic Inpatients - Dhamayanti, Grahyta; Yanti, Imelda; Saptarini, Ika (Sekolah Vokasi Universitas Gadjah Mada, 2025)
Background: Orthopedic surgery is a flagship service at Fatmawati Hospital that demands high complexity and requires accurate clinical documentation and diagnosis coding. Incomplete medical records and coding errors can lead to administrative and financial problems.Objective: This study aims to analyze the association between the completeness of medical record documentation and the accuracy of diagnosis coding in orthopedic inpatients.Methods: A quantitative cross-sectional study was conducted on 95 orthopedic inpatient medical records selected purposively. Data were collected using a documentation completeness checklist and a coding review form based on ICD-10 and ICD-9-CM. Analyses included chi-square tests, Pearson correlation, and logistic regression.Results: Of all medical records, 78.9% were complete and 70.5% had accurate diagnosis coding. Documentation completeness was significantly associated with coding accuracy (χ² = 44.647; p = 0.001). Logistic regression confirmed documentation completeness as a predictor of coding accuracy (p = 0.001; OR = 0.013), accounting for 56.7% of the variance. A strong correlation was also found between coders’ length of work experience and coding accuracy (r = 0.805; p < 0.001).Conclusion: Complete documentation improves diagnosis coding accuracy. Recommendations include the use of standardized checklists, routine coder training, SIMRS optimization, stronger coder–physician collaboration, and regular audits to enhance evidence-based service quality and claims validity.